Applying Heutagogy in Arabic Language Instruction Fostering Learner Autonomy and Digital Literacy / طبيق مدخل الهيوتاغوجيا في تعليم اللغة العربية: نحو تعزيز استقلالية المتعلم والثقافة الرقمية - ibnu fitrianto (IJAS: International Journal of Arabic Studies, 2026)
This study aims to explore the application of the heutagogical approach in Arabic language instruction and its role in fostering learner autonomy and digital literacy in the digital era. The study employed a qualitative method using a library research approach by analyzing books, scholarly articles, and previous studies related to heutagogy, self-determined learning, and Arabic language education. Data were collected from various academic sources and analyzed through content analysis and thematic analysis. The findings indicate that the heutagogical approach contributes to the development of learner autonomy, enhances self-directed learning skills, and promotes digital literacy. Furthermore, it supports critical thinking and lifelong learning among Arabic language learners. The study also reveals that digital technologies and online learning environments provide substantial opportunities for implementing heutagogy in Arabic language instruction. However, several challenges remain, including limitations in digital infrastructure and teachers’ competencies. Therefore, the study recommends integrating heutagogical principles into Arabic language education programs and strengthening the digital competencies of both teachers and learners.